Provision for Old Age. National and International Survey Data to Support Research and Policy on Aging - Hendrik Jürges (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2009)
This report reviews recent trends in the collection of multidisciplinary and longitudinal data in the area of aging research, both in Germany and internationally. It also discusses important developments such as linkage with administrative records, the inclusion of health measurements and biomarkers, and the inclusion of populations in institutions, particularly nursing homes.
Keywords: 330